Application of Biophysical Properties of Meridians in the Visualization of Pericardium Meridian - Feng Xiong; Ruimin Xu; Tongju Li; Jinyu Wang; Qingchuan Hu; Xiaojing Song; Guangjun Wang; Huanhuan Su; Shuyong Jia; Shuyou Wang; Zongxiang Zhu; Weibo Zhang (Medical Association of Pharmacopuncture Institute, 2023)
Background : The biophysical properties of the meridian system, an important concept of traditional Chinese medicine, include low impedance, resounding voice, and high acoustic conductance, all of which are helpful for elucidating the essence of meridians. Objectives: To visualize the human pericardium meridian (PC) based on the resounding voice property of meridians. Methods : Visualization of the PC was performed by injection of fluorescein sodium at the PC6 acupoint (Neiguan) on the PC. Before injection, percussion active points (PAPs) were identified by the virtue of their resounding voice properties. After injection, the trajectories of fluorescein migration throughout the body surface were recorded and analyzed. The distribution of fluorescein in the tissue was further studied using cross-sections of hind limbs of mini-pigs, in which fluorescein was injected into low impedance points. Results : The identified PAP lines were colocalized with PC. Following intradermal fluorescein injection, 1-3 fluorescent lines, which were unrelated to the arm veins, were observed in 7 of 10 participants; 85.4% of fluorescent signals were coincident with PAPs and their intensity had a negative correlation with the body mass index (r = -0.56, p = 0.045). Cross-sections showed a Y-shaped fluorescence pattern where the two migration lines on the surface were the two vertices of the "Y." Conclusion : The trajectories of fluorescein in the body are suggestive of the anatomical structure of meridians. The PC is related to the deep horizontal interstitial channels that connect to the body surface through vertical interstitial spaces. These biophysical properties and techniques for meridian visualization are valuable for revealing the anatomical structure of meridians.